The role of vacancies in the mobility of dislocations and grain boundaries in magnesium - Lambri, Osvaldo Agustin F. (2007)
Vacancy flux or supersaturation enhances grain-boundary mobility, but experimental evidence is not large and in many cases the role of vacancies is only inferred indirectly. We will show effectively in the present work the importance of the vacancy role in grain-boundary mobility in commercial pure and high-purity magnesium using mechanical spectroscopy, electrical resistivity and positron annihilation spectroscopy. It has been found that the mobility decrease of grain boundaries and dislocations is related to vacancy concentration reduction attained after the homogenisation treatment. Indeed, the largest vacancy concentration reduction is observed between 420 and 500 K. Unlocking grain boundaries and dislocations requires new vacancies, generated at temperatures above 500 K. In addition, a new damping peak related to vacancies was discovered at 490 K for an oscillating frequency of 1 Hz.